IMPROVING THE EFFICIENCY OF HYDRAULIC ENGINEERING SYSTEMS BASED ON GEOGRAPHICAL INFORMATION SYSTEMS - Laylo Butt,; Yarbekov Mansur Sobirovich,; Alisherov Isobek Botir o'g'li,; Narzullayeva Nilufar Lutfullo qizi, (TADQIQOTLAR, 2026)
Abstract: Hydraulic engineering systems have always played a critical role in supporting  the  development  of  human  civilization  by  controlling,  storing,  and distributing  water  for  diverse  requirements  such  as  agriculture,  municipal  needs, industrial processes, and environmental sustainability. Over time, the complexity and scope  of  hydraulic  infrastructure  have  expanded  dramatically.  Dams,  reservoirs, irrigation networks, drainage systems, canals, weirs, and soil retention structures all exist to manage the distribution and behavior of water in both natural and artificial landscapes.